Comparison of an Anterior Cruciate Ligament’s Functional Outcomes Peroneus Longus Graft Reconstruction as an Option to the Hamstring Tendon Graft - Mubashir Hassan, Asghar Khan, Babar Shahzad Sadiq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The utilization of peroneus longus graft for the main ACL reconstruction had not been considered since the advent of arthroscopic surgery of anterior cruciate ligament (ACL). There is not much written about it. Therefore, the purpose of this study is for comparison of functional results, morbidity of donor site, knee stability, and evaluation of the muscle of thigh worsening in the patients having the injury of ACL who underwent reconstruction of the arthroscopic single-bundle utilizing the PLT and the HT, respectively. Methods: The crass sectional and survey designed was used to meet the study objectives. The population was Prior to surgery and rehabilitation, all patients who were included were randomly assigned to the HT and PLT groups The 194 individuals whose admitted for the arthroscopic single-bundle ACLR who had symptoms of symptomatic ACL insufficiency and was between the ages of 16 and 50 and of either gender was divided into two groups (hamstring tendon and peroneus longus). Preoperative measurements were taken as well as ones at six months and a year after surgery for functional, clinical knee evaluation, morbidity of donor site, and the thigh circumference. In both groups, the identical post-operative rehabilitation regimen was used. Results: The criteria of inclusion were met by 174 patients. The scores of postoperative, preoperative 6-months, and the 1-year post-operative for hamstring and groups of PL in the IKDC where p = 0.3 and score of the Lysholm knee where p = 0.28 did not differ significantly from each other. The thigh muscle wasting was significantly reduced in group of PLT so at the last follow-up where the p < 0.001, while it was not significantly different in the HT group (mean for the AOFAS was 99.05 ± 3.56 and 99.80 ± 0.70, respectively). Practical implication: This study is for comparison of functional results, morbidity of donor site, knee stability, and evaluation of the muscle of thigh worsening in the patients having the injury of ACL who underwent reconstruction of the arthroscopic single-bundle utilizing the PLT and the HT, respectively. Given that there was no discernible donor site morbidity and improved recovery of the thigh muscle atrophy (better reactivity to the rehabilitation than the HT group), it was an effective and secure autograft choice for routine ACL restoration. Conclusion: Similar knee stability and functional results were seen in both groups, and there was no clear donor site morbidity. Additionally, these patients recovered from the withering of their thigh muscles more quickly after receiving physiotherapy. Therefore, we can suggest that a PL graft may be a reliable, practical, and efficient alternative to the standard arthroscopic single-bundle replacement. Keywords: Hamstring tendon, hamstring tendon grafts, anterior cruciate ligament reconstruction, hamstring tendons, anterior cruciate ligament